Extent of Implementation on the Use of Body Worn Camera in Police Operations: Basis for Enhanced Action Plan - Andrade, Francha; Ayon, Aubrey; Cebrero, Jude; Pagkaliwangan, Joel; Sarte, Roldan; Villa, Elizabeth Buena (Future Science / FSH-PH Publications, 2024)
This study aimed to evaluate the implementation on the use of body worn camera in police operations among police officers in Cebu City. It utilized descriptive comparative analysis, employing survey methods. However, it was confined to only 11 Police Stations in Cebu City. The participants consisted of 50 police officers who were selected to utilize body worn cameras, as well as 50 community people in the study area. The selection process for both groups involved purposive sample technique. The research instrument in this study was a survey questionnaire adopted from the operational guidelines and policies on the use of body worn camera during police operations of the Philippine National Police (2018). All the strands of the implementation on the use of body worn camera in police operations were rated by the respondents based on a 5-point scale. Data were analyzed using mean, and One Way Analysis of Variance. The community and law enforcement have overwhelmingly praised body-worn cameras for their major contribution to the development of good ties between the two groups. Cameras enhance accountability and transparency, thereby boosting public trust in the police force. Nevertheless, questions regarding the implications for privacy and safety persist. The presence of cameras has a beneficial effect on both workers and the community, strengthening public trust, enhancing accountability, and decreasing the use of force. In addition, they furnish substantiation to bolster law enforcement endeavors and settle conflicts. Effective community policing depends on establishing trust, which body-worn cameras help to do.